A review of health and wellness studies involving Inuit of Manitoba and Nunavut. Issue 1 (1st January 2020) - Hayward, Ashley; Cidro, Jaime; Dutton, Rachel; Passey, Kara
ABSTRACT: The purpose of this review is to summarise past Inuit health and wellness studies in Manitoba and the Kivalliq region of Nunavut to provide a snapshot of the types of studies available and identify the gaps in knowledge. Research to date has largely been disease-based and often provides comparisons between Indigenous and non-Indigenous people. Distinct Inuit experiences are rarely written about from an Inuit perspective. However, Inuit Tapiriit Kanatami, the national organisation of Inuit in Canada, and Pauktuutit Inuit Women of Canada have been leaders in strengths-based community research and publications that address priorities determined by the Inuit, including the 2018 Inuit Tapiriit Kanatami document National Inuit Strategy on Research (132).